Curing of complex monomer systems: a spectroscopic and thermal analysis - Martin, Seán J. (Trinity College (Dublin, Ireland). School of Physics, 2001)
This thesis describcs the development of a novel methodology, which uses the high resolution liquid nuclear magnetic resonance (NMR) spectroscopic technique to continuously monitor in real time the thermal and UV-photoinitiated curing dynamics of a range of multi-component monomer systems, comprising mainly of N-vinyl-2- pyrrolidone / 2-hydroxyethyl methacrylate / 4 and 5-t-butyl-2-hydroxycyclohexyl methacrylate (NVP/HEMA/TBE). These systems are of both academic and commercial interest, in this case, in the manufacture of hydrogel contact lenses.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin